Transcriptome Differences Suggest Novel Mechanisms for Intrauterine Growth Restriction Mediated Dysfunction in Small Intestine of Neonatal Piglets - Huang, Shimeng; Wu, Zhenhua; Yuan, Xiongkun; Li, Na; Li, Tiantian; Wang, Junjun; Levesque, Crystal L.; Feng, Cuiping (Frontiers in Physiology, 2020)
Impaired intestinal function is frequently detected in newborns with intrauterine growth restriction (IUGR), while the mechanism between transcriptome profiles and small intestinal dysfunction is still unclear. Therefore, this study was conducted by using IUGR neonatal piglets to uncover the mechanism underlying intestinal dysfunction. Neonatal piglets with IUGR and normal birth weight (NBW) were sacrificed at birth. Transcriptomic sequencing was performed on intestinal samples and generated 18,997 and 17,531 genes in NBW and IUGR group, respectively. A total of 10 differentially expressed genes (DEGs) were identified, of note, only 6 were mapped to the genome reference database, with 2 up-regulated (HSF4 and NR1H4) and 4 down-regulated (BTNL3, BPI, NLRP6 and SLC5A8). Which these DEGs were markedly related to energy metabolism, immune and inflammatory activity. IUGR piglets presented lower concentration of glucose and triglyceride, and higher concentration of cholesterol in plasma, compared with the NBW piglets. Histological analysis revealed decreased mucins and increased apoptosis in both jejunum and ileum for IUGR piglets. Collectively, we found that IUGR induced intestinal dysfunction by altering energy metabolism, immune and inflammatory activity in neonatal piglets, which provides new insights into the prevention and treatment of IUGR.